Effects of Phosphate on Secondary Mineral Formation During the Bioreduction of Akaganeite (β-FeOOH): Green Rust Versus Framboidal Magnetite - J. O'Loughlin, Edward; A. Gorski, Christopher; M. Scherer, Michelle (Current Inorganic Chemistry (Discontinued), 2015)
The activity of microorganisms is a key component of the biogeochemical cycle of Fe in natural systems, where green rusts are often observed as products of microbially driven redox processes. To better define the factors that control green rust formation during microbial Fe(III) reduction, we examined the effects of the presence of an electron shuttle [9,10-anthraquinone-2,6-disulfonate (AQDS)] and phosphate on akaganeite (β-FeOOH) bioreduction by the iron(III)-reducing bacterium (IRB) Shewanella putrefaciens CN32. Framboidal magnetite was the principal secondary mineral formed during akaganeite bioreduction in the absence of phosphate; this is the first time framboidal magnetite has been reported as a product of microbial Fe(III) oxide reduction. Framboidal magnetite was less crystalline when formed in the presence of AQDS than without AQDS and over time was further reduced to chukanovite. Carbonate green rust was the primary secondary mineral observed from akaganeite bioreduction in the presence of phosphate, with and without AQDS; however, siderite was also observed in the presence of AQDS. This first report of green rust as a product of akaganeite bioreduction expands the range of Fe(III) oxides that can be transformed to green rust by IRB, suggesting that the reduction of Fe(III) oxides such as ferrihydrite, lepidocrocite, and akaganeite by IRB is a key process leading to the formation of green rusts in aquatic and terrestrial environments.
Keywords: AQDS